Lamoiyan Cosmetics Laboratory a production systems study - Sy, Bernabeth K.; Tiu, Daniel Y.; Tupaz, Jovi Francis W. (Diliman, Quezon City College of Engineering, 1992)
"Hapee'ng - hapee ang feeling!" Have you ever wondered what goes one inside the company behind this famous commercial phrase? Do you often imagine how a simple 100 mltoothpast tube is manufactured? This Production Systems Study will not only answer most of your inquiries, but will also specifically focus on the aspects of productivity improvement through scheduled maintenance, forecasting, and capacity planning. Sections 1 and 2 will introduce the readers to Lamoiyan Cosmetics Laboratory, makers of Hapee toothpastes and toothbrushes, and the company's ingredients in ensuring high quality, safe, and affordable toothpastes. Section 3 will try to use the data acquired by the group to come up with recommendations and findings that will hopefully prove to be beneficial and advantageous to the company. Sections 4 entitles "Problem Areas" will attempt to identify Lamoiyan's problems and critical areas. And the last section (section 5) will show some improvements and recommendations that can be effectively practiced in order to improve the present system.
IE 151
Feasibility study
Keywords: Lamoiyan Cosmetics Laboratory; Cosmetics industry; Production engineering